Pharmaceutical Industry Driven by Artificial Intelligence and Machine Learning - Sandha Udhan Baorhide (Multidisciplinary Journal of Akseprin Indonesia, 2025)
Artificial Intelligence (AI) and Machine Learning (ML) are transforming the pharmaceutical industry at all phases—drug research, development, regulatory compliance, quality assurance, and post-marketing monitoring. These technologies enhance data processing, precision, and timeliness through the utilisation of intricate algorithms and extensive healthcare datasets. Artificial intelligence aids in drug target identification, drug design, toxicity prediction, and pharmacokinetics modelling, while also enhancing regulatory processes and pharmacovigilance. Despite its advantages, difficulties persist, including data privacy, algorithmic bias, explainability, and accountability. Regulatory frameworks and ethical considerations must evolve to ensure the safe and equitable application of AI in pharmaceuticals. This article examines the current applications, benefits, hazards, and future potential of AI and ML in revolutionising medication development and healthcare outcomes.